The relationship between government expenditure and poverty: A cointegration analysis - Rashid Mehmood; Sara Sadiq (Romanian Journal of Fiscal Policy (RJFP), 2010)
The study examines the long run as well as short run relationship between the fiscal deficits, which is outcome of high government expenditure over the level of tax revenue collection, and poverty. The results reveal a negative relationship between government expenditure and poverty based on time series data from 1976 to 2010. The short run and long run relationships between poverty and other variables are identified by ECM model and Johnson Cointegration test respectively. The results show that there exist short run as well as long run relation between the poverty and government expenditure.
Keywords: H50; I30; 330; government expenditure; poverty